Optimizing Jasmine Flower Extraction: A Review of Modern Approaches - , Syed Mazar Ali; , Uday kumar Nidoni; , Krishna Reddy G. S (Archives of Current Research International, 2025)
Jasmine, renowned for its enchanting fragrance and therapeutic properties, holds significant cultural, economic, and industrial value globally. Primarily cultivated for its flowers, jasmine is widely used in perfumery, cosmetics, aromatherapy, and pharmaceuticals. Value addition, such as producing essential oils, teas, and skincare products, enhances profitability, extends shelf life, and reduces post-harvest losses. Traditional extraction methods like steam distillation (SD) and solvent extraction (SE) face limitations, including low yield, long extraction times, and degradation of heat-sensitive compounds. To overcome these challenges, innovative technologies such as supercritical fluid extraction (SFE), microwave-assisted extraction (MAE), ultrasound-assisted extraction (UAE), subcritical water extraction (SWE), pulsed electric field (PEF), and cold plasma extraction have emerged. These methods offer higher efficiency, improved yield, and reduced environmental impact. For example, SFE using supercritical CO₂ achieves superior oil yields, while MAE and UAE reduce extraction time and energy consumption. SWE eliminates organic solvents, making it a sustainable alternative, and PEF and cold plasma enhance extraction by disrupting cell membranes. Despite their advantages, challenges such as high equipment costs, scalability, and optimization of parameters remain. Future research should focus on techno-economic analysis, environmental impact assessment, and scalable industrial prototypes. By integrating these advanced technologies, the jasmine industry can achieve sustainable growth, support rural livelihoods, and meet the rising demand for natural and organic products. This review highlights advancements in jasmine processing, emphasizing the potential of innovative extraction methods to revolutionize the industry while preserving its aromatic and therapeutic qualities.